UPAYA MENINGKATKAN KEMAMPUAN GURU-GURU SD CAMPAGO IPUH BUKITTINGGI DALAM PEMBELAJARAN SENI RUPA DAN KERAJINAN - Wisdiarman Wisdiarman; Suib Awrus; Idran Wakidi; Irwan Irwan (Ranah Seni, 2018)
Abstract One of the material in the Culture and Craft Arts curriculum at Elementary Schoolis fine arts and crafts. Teachers at Campago Ipuh Elementary SchoolMandiangin Koto Selayan Bukittinggi had problems in learning. Teachers in Elementary Schools have not been able to carry out art and craft learning, in terms of this learning inElementary Schools is the most effective means for the formation of personal children. This is because, besides not having a special educational background in fine arts and crafts, there are other reasons; the teacher does not master art and craft material. Based on the above problems, sothe priority problems to be solved were related to the mastery of material learning in arts and crafts, with the formulation of the problem being; the lack of the teacher’s abilityinElementary SchoolCampago Ipuh Mandiangin Koto Selayan Bukittinggi inmasteringart and craft materials. Therefore,an activity is carried out which thepurpose is to improve the ability of teachers in learning arts and crafts at Elementary SchoolCampago Ipuh Mandiangin Koto Selayan Bukittinggi. Solutionof these problems is done by counseling, training, and mentoring. The results of this activity are 1) in general,Elementary School teachers have mastered fine art material (reliefprint) well, 2) in general,Elementary School teachers have mastered craft material (makrame craft) well.